2021
DOI: 10.3389/fpls.2021.711838
|View full text |Cite
|
Sign up to set email alerts
|

Plasmodiophora brassicae-Triggered Cell Enlargement and Loss of Cellular Integrity in Root Systems Are Mediated by Pectin Demethylation

Abstract: Gall formation on the belowground parts of plants infected with Plasmodiophora brassicae is the result of extensive host cellular reprogramming. The development of these structures is a consequence of increased cell proliferation followed by massive enlargement of cells colonized with the pathogen. Drastic changes in cellular growth patterns create local deformities in the roots and hypocotyl giving rise to mechanical tensions within the tissue of these organs. Host cell wall extensibility and recomposition ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…The PMEI region of AtPMEI-PME3 could protect pectin in the golgi apparatus from premature de-methylesterification. CW remodeling of Arabidopsis root cells is also exploited by the obligate biotrophic Plasmodiophora brassicae, a protist pathogen that causes clubroot disease in brassica species (Stefanowicz et al, 2021). A pectin de-methylesterification mediated by AtPMEI-PME18 can favor the release of resting spores of the fungus.…”
Section: Pmeis Are Involved In Multiple Biotic and Abiotic Stressesmentioning
confidence: 99%
“…The PMEI region of AtPMEI-PME3 could protect pectin in the golgi apparatus from premature de-methylesterification. CW remodeling of Arabidopsis root cells is also exploited by the obligate biotrophic Plasmodiophora brassicae, a protist pathogen that causes clubroot disease in brassica species (Stefanowicz et al, 2021). A pectin de-methylesterification mediated by AtPMEI-PME18 can favor the release of resting spores of the fungus.…”
Section: Pmeis Are Involved In Multiple Biotic and Abiotic Stressesmentioning
confidence: 99%
“…Gene families were investigated in such large data approaches such as UDP-glucosyltransferases [ 97 ], sugar transporter families, including STP and SWEET [ 98 , 99 ], invertase [ 100 ], chitinase [ 101 ], auxin conjugating GH3 genes [ 102 ], pectin-related genes [ 103 ], as well as functional pathways, e.g., flavonoids [ 38 , 104 ] or glucosinolates [ 105 ]. Other defense-related pathways including hormones will be discussed below (see Section 5.4 ).…”
Section: Transcriptome and Posttranscriptional Regulationsmentioning
confidence: 99%
“…Interestingly, an expansin was also on the gene list that was altered after the overexpression of the P. brassicae effector PBZF1 in A. thaliana [ 77 ]. Other cell-wall modifying proteins are encoded by pectin methylesterases, which were analyzed for their role during clubroot development [ 103 ] based on the dataset from [ 80 ]. Functional analyses confirmed that the club development in a pme18 mutant was altered, namely cell wall enlargement was reduced.…”
Section: Transcriptome and Posttranscriptional Regulationsmentioning
confidence: 99%
“…Pectins are galacturonic acid (GalA) - containing polysaccharides among which the linear polymer homogalacturonan (HG) is the most abundant matrix polysaccharide, for instance representing 20% of the total cell wall polysaccharides, in Arabidopsis thaliana leaves (Zablackis et al, 1995) or even 50% in onion epidermis cells (Wilson et al, 2021). In vivo studies show that the metabolism of HG plays a critical role in the control of cell expansion and plant morphogenesis (Andres-Robin et al, 2018; K. T. Haas et al, 2020; Jobert et al, 2021; Peaucelle et al, 2015, 2008; Phyo et al, 2017; Qi et al, 2017; Stefanowicz et al, 2021; Wachsman et al, 2020) but the underlying mechanisms are still poorly understood.…”
Section: Introductionmentioning
confidence: 99%